Clinical use of measurable residual disease in adult ALL: recommendations from a panel of US experts - Nicholas J. Short; Ibrahim Aldoss; Daniel J. DeAngelo; Marina Konopleva; Jessica Leonard; Aaron C. Logan; Jae Park; Bijal Shah; Wendy Stock; Elias Jabbour (Blood Advances)
Abstract: Measurable residual disease (MRD) is a powerful predictor of clinical outcomes in acute lymphoblastic leukemia (ALL). In addition to its clear prognostic importance, MRD information is increasingly used in clinical decision algorithms to guide therapeutic interventions. Although it is well established that achievement of MRD-negative remission is an important end point of ALL therapy, the prognostic and therapeutic implications of MRD in an individual patient are influenced by both disease-related factors (eg, cytomolecular risk) and assay-related factors (eg, sensitivity, specimen source, and timing of assessment), which add complexity to MRD-guided treatment decisions. In this review, we discuss the data supporting the use of MRD assessment in adult ALL and how this information can rationally inform clinical decisions, including selection of patients for MRD-directed therapies or allogeneic hematopoietic stem cell transplantation. We also discuss important interpretative challenges related to novel high sensitivity next-generation sequencing–based MRD assays, which are becoming increasingly used in clinical practice.